0162 Prevalence of occupational exposure to lead in Australia. (23rd June 2014) - Driscoll, Tim; Carey, Renee; Glass, Deborah; Benke, Geze; Peters, Susan; Reid, Alison; Fritschi, Lyn
Abstract : Objectives: To determine the prevalence of work-related exposure to lead, the main circumstances of work-related exposure to lead in the general workforce, and the use of workplace control measures designed to decrease exposure to lead, in Australia. Method: The information came from the Australian Work Exposures Study (AWES) project, a nationwide survey which investigated the current prevalence of work-related exposure to 38 known or suspected carcinogens, including lead, among Australian workers, based on reported job tasks. Only those persons designated as having probable work-related exposure to lead were included in the analysis. Assessments were extrapolated to the national workforce with reference to the 2011 Census. Results: The results suggest approximately 6.6% of Australian workers were occupational exposed to lead. Almost all exposed workers were male, about half workers worked in technical occupations and almost half worked in the construction industry. The main tasks associated with probable exposures were, in decreasing order, soldering; painting old houses, ships or bridges; plumbing work; cleaning up or sifting through the remains of a fire; radiator repair work; machining metals or alloys containing lead; mining; and welding leaded steel. The use of appropriate respiratory control measures was inconsistent. Exposure levels were assessed as being high or medium in most cases, taking into account information on work tasks and the controls being used by workers. Conclusions: The study suggests exposure to lead in the Australian workforce is higher than expected based on estimates from other countries. There is considerable scope for better use of exposure control measures.